A decade of research on genetic privacy: the findings of the GetPreCiSe Center at Vanderbilt University - Slobogin, Christopher; Tellis, Karli; Clayton, Ellen Wright; Clayton, Jay; Eilmus, Ayden; Malin, Bradley A. (Frontiers in Genetics, 2025)
Research carried out by Vanderbilt University’s and Medical Center’s federally-funded transdisciplinary, highly interactive GetPreCiSe Center in Excellence for ELSI research on genomic privacy—involving over 40 scholars across computer and social sciences, law, and the humanities—is summarized by dividing the work into five categories: (1) the nature of risks posed by collection of genetic data; (2) legal and scientific methods of minimizing those risks; (3) methods of safely increasing the scope of genetic databases; (4) public perceptions of genetic privacy; and (5) cultural depictions of genetic privacy. While this research shows that the risk of unauthorized re-identification is often over-stated, it also identifies possible ways privacy can be compromised. Several technical and legal methods for reducing privacy risks are described, most of which focus not on collection of the data, but rather on regulating data security, access, and use once it is collected. Researchers also collected empirical data assessing the public’s views on genomic privacy. This research indicated that public concern about genetic privacy may be no greater than concern about financial and other types of privacy and often varies depending on the context in which the information is accessed. More generally, the research suggested that privacy experts may underestimate the extent to which the public values utility over privacy risk. Finally, both survey data and research on media depictions about genetic science found that worry about genetic research and its impact on privacy and other values appear to grow as the time horizon lengthens and varies significantly based on demography; in particular, minority groups defined by ethnicity and sexual identity are more anxious about genetic disclosures than other groups. Research looking at fan fiction, blog posts, and online book reviews also found that these depictions can have a direct impact on public attitudes about genetic science.